ASSESSING USER SATISFACTION OF SMART PARKING PAYMENT SYSTEM IN SELANGOR (Journal of Digital System Development, 2025)
The Smart Selangor Parking (SSP) app aims to enhance digital adoption in Selangor's journey toward becoming a livable smart state. However, user satisfaction with the app remains unclear, raising concerns about its effectiveness in fostering economically productive and environmentally conscious communities. The research question is: What factors significantly influence user satisfaction with the SSP application? Thus, the objectives are to identify the factors influencing user satisfaction with SSP and determine which factors have the most significant impact. This analysis aims to provide insights into areas that require improvement to enhance the app's effectiveness and adoption. This study follows a quantitative design to assess user satisfaction with the SSP app. It includes three phases: definition, exploratory, and confirmation. In the definition phase, the research problem and objectives are set. The exploratory phase involves collecting data and refining the research questions. The confirmation phase rigorously tests hypotheses using statistical techniques. Validation activities ensure the reliability and validity of the findings, such as ensuring accurate measurements and testing the consistency of data collection methods. The findings revealed that user satisfaction with the Smart Selangor Parking app is most influenced by learnability, which ensures ease of use and minimises distractions. Helpfulness also plays a significant role, as providing relevant information enhances user satisfaction. Emotional attachment, controllability, and efficiency were also factors, though efficiency had the least impact. Overall, this study emphasises the importance of usability, clear information, and user-centred design in enhancing satisfaction. This study contributes to understanding factors influencing user satisfaction with mobile parking payment applications in Malaysia, offering valuable insights for developers and policymakers. It highlights the importance of usability, user perceptions, and barriers to adoption, guiding future research and enhancing the effectiveness of mobile payment systems for parking.